MPCs through COVID: Spending, saving and private transfers - Thomas F. Crossley; Paul Fisher; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2020)
MPCs were directly elicited from a representative sample of UK adults in July 2020. Reported MPCs are low, around 11% on average. They are higher, but still modest, for individuals in households with high current needs. These low MPCs may be a consequence of the prevailing economic uncertainty. Some respondents report that they would respond to a one-time income payment by transferring more to friends and family, others report they would see a decline in the payments received. Targeting payments to high-MPC individuals could be partly undone. Further, the aggregate MPC out of a stimulus payment need not equal the population-average MPC, even if all individuals receive the same payment.
Keywords: D12; D14; E21; 330; COVID-19; spending; MPC; crowding out